2007
DOI: 10.1080/03235400600586716
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reduviid predators and plant products against chosen groundnut pests

Abstract: The augmentative release of a reduviid predator Rhynocoris kumraii Ambrose and Livingstone (Heteroptera: Reduviidae), hot water extract of Ipomea cornea Jacq. (Family Convvolulaceae) and Vitex negundo Linn. (Family Verbenaceae) were evaluated against selected groundnut pests at farmers field in Tamil Nadu, India. The results revealed that invariably endosilfan highly reduce all the pest populations. Aphis craccivora (Koch) (Hemiptera: Aphididae) population was highly reduced by the combination of both plant ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Similarly, biological control potential of A. pedestris on H. armigera was recorded in lady's finger orchards (Sahayaraj and Ravi 2007). Recent studies by revealed that R. marginatus could be used as augmented biological control agent for groundnut.…”
Section: Augmentative Biological Controlmentioning
confidence: 97%
“…Similarly, biological control potential of A. pedestris on H. armigera was recorded in lady's finger orchards (Sahayaraj and Ravi 2007). Recent studies by revealed that R. marginatus could be used as augmented biological control agent for groundnut.…”
Section: Augmentative Biological Controlmentioning
confidence: 97%
“…Despite the natural abundance of assassin bugs and their importance as predators of invertebrates in agricultural and other ecosystems (31)(32)(33), the detailed composition of assassin bug venom remains unknown. Here, we elucidate the protein composition of venom from the harpactorine assassin bug Pristhesancus plagipennis using a combined transcriptomic/proteomic approach.…”
mentioning
confidence: 99%
“…In other similar studies, field releases of P. plagipennis and R. marginatus were successful in reducing S . litura, H. armigera and A. craccivora populations in cotton and groundnut fields . However, there are no reports available concerning the utilization of an augmentative release of R. fuscipes for cotton pest management.…”
Section: Discussionmentioning
confidence: 99%